Sharia Financial Mindfulness as a Predictor of Halal Investment Decisions Among Muslim Millennials - Moh. Ainur Rosyid (PAPUA: International Journal of Sharia Business Management, 2025)
This study explores Sharia Financial Mindfulness as a significant predictor of halal investment decisions among Muslim millennials. The central problem addressed is the lack of internal, faith-based psychological constructs in existing research on Islamic investment behavior, which has primarily focused on external factors such as financial literacy and religiosity. Adopting a qualitative research approach, the study involved in-depth, semi-structured interviews with 15 Muslim millennials who actively invest in halal financial products such as sukuk, Islamic mutual funds, and Sharia-compliant fintech platforms. Data were analyzed using thematic analysis to identify key dimensions of mindfulness in financial decision-making. The findings revealed four major themes: (1) a conscious alignment between faith and finance, (2) ethical reflection as a motivation for investment, (3) the dual role of digital platforms as both facilitators and disruptors of mindfulness, and (4) the internalization of Sharia values as a source of financial discipline. The research concludes that Sharia Financial Mindfulness activates components of the Theory of Planned Behavior—attitude, subjective norms, and perceived behavioral control—thus forming a cognitive foundation for value-driven investment behavior. This study offers both theoretical advancement and practical guidance for Islamic finance stakeholders aiming to cultivate spiritually grounded investors.